2017
DOI: 10.1158/0008-5472.can-17-0357
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Jagged Immunotherapy Inhibits MDSCs and Overcomes Tumor-Induced Tolerance

Abstract: Myeloid-derived suppressor cells (MDSCs) are a major obstacle to promising forms of cancer immunotherapy, but tools to broadly limit their immunoregulatory effects remain lacking. In this study, we assessed the therapeutic effect of the humanized anti-Jagged1/2 blocking antibody CTX014 on MDSC-mediated T cell suppression in tumor-bearing mice. CTX014 decreased tumor growth, impacted the accumulation and tolerogenic activity of MDSCs in tumors, and inhibited the expression of immunosuppressive factors arginase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 49 publications
7
66
0
Order By: Relevance
“…Notch and NF-κB profiles may contribute to identify patients and tumors likely to respond to immunotherapy and to provide a new alternative approach to nonresponders. Promising therapies implied that Notch modulation (anti-Jagged1/2) combined with novel immune checkpoint blockade therapies ( 108 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notch and NF-κB profiles may contribute to identify patients and tumors likely to respond to immunotherapy and to provide a new alternative approach to nonresponders. Promising therapies implied that Notch modulation (anti-Jagged1/2) combined with novel immune checkpoint blockade therapies ( 108 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, tumor immunogenicity regulated by DDR pathways might be enhanced by NOTCH1 inhibition (22), possibly via the direct binding between NOTCH1 and ataxiatelengiectasia mutated (ATM) (24,25). Thirdly, in immune microenvironment, the NOTCH ligands on myeloid-derived suppressor cells (MDSCs) interact with the NOTCH receptor on tumor cells and thereby improve the CSC capacity (26), which in turn increases the expression of NOTCH ligands on MDSCs (27), constituting a positive feedback eventually resulting in immune tolerance (28). Based on these observations, we hypothesized that NOTCH mutation in NSCLC might predict the clinical benefit from immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Rodriguez lab in collaboration with the Miele and Osborne labs showed that tumor MDSC, unlike circulating MDSC, upregulate expression of Notch ligand Jagged1, and to a lesser extent, Jagged2. This phenomenon is mediated by NF-κB ( 39 ). Treatment with an anti-Jagged1/2-blocking antibody had remarkable therapeutic activity in several mouse models (3LL lung carcinoma and EG-7, an ovalbumin-expressing form of EL-4 lymphoma), which depended upon enhanced CD8 responses ( 39 ).…”
Section: Notch and Mdscmentioning
confidence: 99%
“…This phenomenon is mediated by NF-κB ( 39 ). Treatment with an anti-Jagged1/2-blocking antibody had remarkable therapeutic activity in several mouse models (3LL lung carcinoma and EG-7, an ovalbumin-expressing form of EL-4 lymphoma), which depended upon enhanced CD8 responses ( 39 ). In EG-7 tumors, anti-Jagged antibodies enhanced the effect of anti-ovalbumin adoptive T-cell therapy (ACT).…”
Section: Notch and Mdscmentioning
confidence: 99%